Phenotypic plasticity in growth and fecundity induced by strong population fluctuations affects reproductive traits of female fish - Karjalainen, Juha; Urpanen, Olli; Keskinen, Tapio; Huuskonen, Hannu; Sarvala, Jouko; Valkeajärvi, Pentti; Marjomäki, Timo J. (Wiley-Blackwell, 2016)
Fish are known for their high phenotypic plasticity in life-history traits in relation to environmental variability, and this is particularly pronounced among salmonids in the Northern Hemisphere. Resource limitation leads to trade-offs in phenotypic plasticity between life-history traits related to the reproduction, growth, and survival of individual fish, which have consequences for the age and size distributions of populations, as well as their dynamics and productivity. We studied the effect of plasticity in growth and fecundity of vendace females on their reproductive traits using a series of long-term incubation experiments. The wild parental fish originated from four separate populations with markedly different densities, and hence naturally induced differences in their growth and fecundity. The energy allocation to somatic tissues and eggs prior to spawning served as a proxy for total resource availability to individual females, and its effects on offspring survival and growth were analyzed. Vendace females allocated a rather constant proportion of available energy to eggs (per body mass) despite different growth patterns depending on the total resources in the different lakes; investment into eggs thus dictated the share remaining for growth. The energy allocation to eggs per mass was higher in young than in old spawners and the egg size and the relative fecundity differed between them: Young females produced more and smaller eggs and larvae than old spawners. In contrast to earlier observations of salmonids, a shortage of maternal food resources did not increase offspring size and survival. Vendace females in sparse populations with ample resources and high growth produced larger eggs and larvae. Vendace accommodate strong population fluctuations by their high plasticity in growth and fecundity, which affect their offspring size and consequently their recruitment and productivity, and account for their persistence and resilience in the face of high fishing mortality.
Keywords: age of maturation; coregonids; embryonic development; fisheries; larval development; maternal effect; stock fluctuations; Vendace coregonus albula; life history traits; reaction norms; local adaptation; atlantic salmon; offspring size; larval size; egg size; age; recruitment